The awkward rhetoric of Spanish liberalism: The politics of language of the Citizens party. - Rosales, José María (John Benjamins Publishing, 2025)
This article explores the ideological controversies around Spanish liberalism through the story of the Citizens party – from its rise in 2006 through 2023, after a sequence of electoral defeats that almost certified its demise. Born as a regional party in Catalonia with an anti-nationalist platform focused on linguistic policies, in national politics it fostered a liberal agenda. The article examines Citizens’ politics of language hiding the party’s liberal identity because of its association to right-wing outlooks. At its founding documents there was an amalgam of liberal and social democratic constitutional values inspiring the party’s political approach. No earnest question was made of their difficult accommodation, given their disparity at the policy level. In 2017 an internal debate arouse, and from 2019 a number of electoral setbacks accelerated it. By then the liberal language legitimizing its passage from regional into a national party had lost its civic appeal.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/10964
Keywords: Liberalismo - España; Retórica - Aspectos políticos; Comunicación en política; Political language; Liberalism; Social democracy; Citizens party; Spanish politics